Revisiting Bap Multidomain Protein: More Than Sticking Bacteria Together - Valle, Jaione; Fang, Xianyang; Lasa, Iñigo (Frontiers in Microbiology, 2020)
One of the major components of the staphylococcal biofilm are surface proteins that assemble as scaffold components of the biofilm matrix. Among the different surface proteins able to contribute to biofilm formation, this review is dedicated to the Biofilm Associated Protein, Bap. Bap is part of the accessory genome of S. aureus but orthologs of Bap in other staphylococcal species belong to the core genome. When present, Bap promotes adhesion to abiotic surfaces and induces strong intercellular adhesion by self-assembling into amyloid like aggregates in response to the levels of calcium and the pH in the environment. During infection, Bap enhances the adhesion to epithelial cells where it binds directly to the host receptor Gp96 and inhibits the entry of the bacteria into the cells. To perform such diverse range of functions, Bap comprises several domains, some of them include several motifs associated to distinct functions. Based on the knowledge accumulated with the Bap protein of S. aureus, this review aims to summarize the current knowledge of the structure and function properties of each domain of Bap and their contribution to Bap functionality.